Respons Audiens Terhadap Isu-Isu Kontroversial pada Akun Instagram Pinrang_info - Aripai, Reski; Hilmiyah, Mifda (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This article aims to explore how the audience of Pinrang_info responds to controversial issues shared on the account. Does the audience tend to offer support or voice protests? The study analyzes audience responses to content shared on the Pinrang_info Instagram account, collected through comments, likes, and shares on each post discussing controversial topics. The analysis seeks to identify patterns in audience interactions, including positive, negative, or neutral sentiments expressed in their comments, as well as categorize audience responses by type. The Pinrang_info Instagram account serves as a platform for voicing controversial issues emerging in society, with an emphasis on criticism of law enforcement, social injustice, and the abuse of power. Audience responses indicate that social media increasingly serves as a channel for the public to express their concerns. Although the responses vary between serious and humorous, the audience tends to accept and agree with the posts shared.